Comparison of Natural Course between Thyroid Cancer Nodules and Thyroid Benign Nodules - Kyun-Jin Yun; Jeonghoon Ha; Min-Hee Kim; Ye Young Seo; Mee Kyoung Kim; Hyuk-Sang Kwon; Ki-Ho Song; Moo Il Kang; Ki-Hyun Baek (Endocrinology and Metabolism, 2019)
BackgroundThe natural course of thyroid cancer nodules and benign nodules is different. This study was to compare the changes in size between thyroid cancer nodules and thyroid benign nodules. The risk factors associated with the changes of thyroid cancer nodules were assessed.MethodsThis study contains retrospective observational and prospective analysis. A total of 113 patients with 120 nodules were recruited in the cancer group, and 116 patients with 119 nodules were enrolled in the benign group. Thyroid ultrasonography was performed at least two times at more than 1-year interval.ResultsThe mean follow-up durations were 29.5±18.8 months (cancer group) and 31.9±15.8 months (benign group) (P=0.32). The maximum diameter change in length was 0.36±0.97 mm/year in the cancer group and –0.04±0.77 mm/year in the benign group (P<0.01). The volume was significantly increased in the cancer group compared with the benign group (0.06±0.18 mL/year vs. 0.004±0.05 mL/year, respectively, P<0.01; 26.9%±57.9%/year vs. 1.7%±26.0%/year, P<0.01). Initial maximum diameter (β=0.02, P<0.01) and initial volume (β=0.13, P<0.01) were significantly associated with volume change (mL)/year. Initial maximum standardized uptake value did not predict the nodule growth.ConclusionIt is suggested that thyroid cancer nodules progress rapidly compared with benign nodules. Initial size and volume of nodule were independent risk factors for cancer nodule growth.